The Effectiveness of Animated Videos and Quizizz on Learning Outcomes in Natural and Social Sciences Among Fourth-Grade Elementary Students - Reva Reva; Abdul Rahman; Nuraini Nuraini; Nashrullah Nashrullah; Dyah Aini Purbarani (Journal of Innovation and Research in Primary Education, 2026)
This study investigates the effectiveness of animated videos and Quizizz on student learning outcomes in Natural and Social Sciences (IPAS) among fourth-grade elementary students. A quasi-experimental design with nonequivalent control group pretest-posttest was employed, involving 40 students at SD Negeri 8 Mamboro divided into experimental (n=20) and control (n=20) groups. The experimental group received instruction through animated videos and Quizizz, while the control group continued with conventional methods over three weeks. Data were collected using validated achievement tests (Cronbach's α = 0.767) and analyzed through Mann-Whitney U and Wilcoxon Signed-Rank tests. Results revealed significant differences between groups, with the experimental group achieving superior posttest performance (M = 76.75, SD = 11.154) compared to controls (M = 65.00, SD = 15.728), confirmed by Mann-Whitney U test (U = 104.000, p = 0.009). Normalized gain analysis demonstrated moderate effectiveness for the experimental group (N-Gain = 0.4876) versus low effectiveness for controls (N-Gain = 0.2688). Completion rates improved substantially from 5% to 60% in the experimental group, compared to 10% to 25% in controls. These findings support cognitive theory of multimedia learning and self-determination theory, demonstrating that integrated implementation of animated videos and Quizizz significantly enhances elementary science learning outcomes through dual-channel information processing and gamified assessment that sustains motivation and engagement.